Frances Amelia Thomas' scrapbook of artworks, poems and music, 1835-1840 - Skipper, John Michael, 1815-1883; Skipper, Frances Amelia, 1815-1855 (1835)
The scrapbook contains drawings, paintings, poetry, stories and sheet music by both Skipper and Thomas. Locations include South Australia.
Title devised by cataloguer based on inscription and acquisition documentation, see file NLA03/1285.
Inscriptions: "Francis Amelia Thomas August 1837 from J.M.S."--In ink on front flyleaf; "Album with drawings & paintings by the late J.M. Skipper, exhibited by Mrs Edwards"--In ink on card.
Condition: Pages torn, stained and foxed. Binding detached.
Also available online
Purchased from Hordern House Rare Books, 2009.
Frances Amelia Thomas met her future husband, John Michael Skipper on board the ship Africaine, which arrived in Holdfast Bay on the 6th November 1836. Frances was the elder daughter of Robert and Mary Thomas a pioneering family in South Australia. John was a solicitor from a well connected Norfolk legal family and accomplished artist. They married in 1839. John and Frances went on sketching trips together and both exhibited paintings in the Exhibition of Colonial Artists in Adelaide in 1847.
Keywords: Women -- Pictorial works; Ships -- Pictorial works; South Australia -- Pictorial works